Traumatic dental injury during yoga practice - Anjali Deshpande; Purva Chaudhari (Wolters Kluwer Medknow Publications, 2017)
With increasing popularity of yoga as a preventive health practice and therapeutic modality, issues regarding its safety have been analyzed in the scientific literature. Overuse, injury or strain, and sprain are some adverse effects that may be attributed to faulty yoga practice. However, traumatic dental injury as a result of fall during yoga practice is rare and unusual. This article presents a case of an 11-year-old female who fractured her permanent central incisor while practicing yoga posture Kukkutasana (cockerel pose), the arm-balancing posture. She underwent root canal treatment for the fractured tooth followed by restoration with post and core crown buildup. Yoga is known as a source of healing since ancient time, which should not cause any harm. It is recommended to adopt appropriate safety measures while performing yoga practices so that the detrimental physical, psychological, and financial consequences of preventable traumatic injuries can be avoided.